2015
DOI: 10.2147/cia.s88404
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, loss, and social support among cognitively intact older people with cancer, living in nursing homes – a mixed-methods study

Abstract: Background: Loneliness is a significant psychosocial effect following a cancer diagnosis and may prevent people from engaging in social activities, thus creating difficulties in interpersonal relationships. This study investigated loneliness and social support among cognitively intact nursing home residents with cancer by using a quantitatively driven mixed-methods design with sequential supplementary qualitative components. Methods:The quantitative component consisted of face-to-face interviews of 60 nursing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 43 publications
1
50
0
2
Order By: Relevance
“…Our findings on the role of aging in loneliness support other qualitative work in older adults that also reported the contribution of age-related disabilities (Finlay & Kobayashi, 2018;Li, Xu, & Chi, 2018) and shrinking social network (Finlay & Kobayashi, 2018;Li et al, 2018;Wong et al, 2017), though the adaptation to aging has not been observed. Similarly, other studies have reported ways in which older adults cope with loneliness, such as keeping busy by oneself (Drageset et al, 2015;Stanley et al, 2010) and doing activities interacting with others (Drageset et al, 2015;Finlay & Kobayashi, 2018). An Australian study reported benefits to being alone, which aligned with our characterization of oneliness or comfort with solitude, as a time to self-reflect and conduct spiritual activities (Stanley et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Our findings on the role of aging in loneliness support other qualitative work in older adults that also reported the contribution of age-related disabilities (Finlay & Kobayashi, 2018;Li, Xu, & Chi, 2018) and shrinking social network (Finlay & Kobayashi, 2018;Li et al, 2018;Wong et al, 2017), though the adaptation to aging has not been observed. Similarly, other studies have reported ways in which older adults cope with loneliness, such as keeping busy by oneself (Drageset et al, 2015;Stanley et al, 2010) and doing activities interacting with others (Drageset et al, 2015;Finlay & Kobayashi, 2018). An Australian study reported benefits to being alone, which aligned with our characterization of oneliness or comfort with solitude, as a time to self-reflect and conduct spiritual activities (Stanley et al, 2010).…”
Section: Discussionmentioning
confidence: 75%
“…Specifically, loneliness is defined as subjective distress resulting from a discrepancy between desired and actual relationships (Ernst & Cacioppo, 1999), while social isolation is the objective lack of social contacts and interactions (Cornwell & Waite, 2009;Gardner, Brooke, Ozanne, & Kendig, 1999). Loneliness may be modifiable, and person-focused interventions are an important but underdeveloped approach (Perissinotto, Holt-Lunstad, Periyakoil, & Covinsky, 2019) Several published papers have focused on the qualitative experience of loneliness among overseas or immigrant populations (Wong, Chau, Fang, & Woo, 2017), medically ill persons (Drageset, Eide, Dysvik, Furnes, & Hauge, 2015;Sj€ oberg, Edberg, Rasmussen, & Beck, 2019), and people at highest risk for loneliness (Neves, Sanders, & Kokanovi c, 2019). However, there is little published literature on qualitative studies of loneliness among independent living older adults in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Specific measures of social support can include structural features (size and composition of network), frequency of interactions, content and quality of support, and perceptions of adequacy (Siebert, Mutran, & Reitzes, 1999). Having adequate social support has been shown to increase positive outcomes for older adults specifically in the areas of long term care, health, community participation, security, and sustained independent living (Antonucci & Akiyama, 1987;Drageset et al, 2015;World Health Organizations, 2002). Research suggests that both giving and receiving social support is important for the well-being of older adults (Thomas, 2009).…”
Section: Social Supportmentioning
confidence: 99%
“…Research suggests that both giving and receiving social support is important for the well-being of older adults (Thomas, 2009). In a study of nursing home residents with cancer, Drageset et al (2015) found that social support that reinforces self-esteem and worth can reduce loneliness.…”
Section: Social Supportmentioning
confidence: 99%
See 1 more Smart Citation